PENGARUH CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN: CORPORATE SOCIAL RESPONSIBILITY SEBAGAI VARIABEL INTERVENING - Lestari, Yuni Tri; Asyik, Nur Fadjrih (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to examine the influence of corporate governance which is proxy by the ownership of managerial stock, the ownership of institutional stock, the size of board of commissioner, and the audit committee to the financial performance of the company with corporate social responsibility as the intervening variable. The samples and have obtained Sustainability Reporting Award (SRA) which is determined by National Center for Sustainability Reporting (NSCR) in 2011-2013 periods. It can be concluded from the result of analysis that corporate governance which is proxy by the ownership of managerial stock, the ownership of institutional stock, the size of board of commissioner, and the audit committee are do not have any significant influence to the corporate social responsibility. The corporate governance has significant influence to the ownership of institutional stock, the size of board of commissioner, and the corporate social responsibility. The ownership of managerial stock and audit committee does not have any significant influence to the financial performance. The result of the research shows that corporate social responsibility is not the intervening variable under the influence of corporate governance to the financial performance.Keywords: Corporate Governance, Corporate Social Responsibility, and Financial Performance